2009
DOI: 10.1016/j.urolonc.2009.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Defining high quality health care

Abstract: Most health care quality improvement efforts target measures of health care structures, processes, and/or outcomes. Structural measures examine relatively fixed aspects of health care delivery such as physical plant and human resources. Process measures, the focus of the largest proportion of quality improvement efforts, assess specific transactions in clinical-patient encounters, such as use of appropriate surgical antibiotic prophylaxis, which are expected to improve outcomes. Outcome measures, which compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 40 publications
0
37
0
2
Order By: Relevance
“…Despite reporting substantial challenges to delivering care, a majority of physicians felt they were able to deliver high quality care. This divergence is likely related to physicians defining high quality care outside of the domains of care assessed in our study 28,29 .…”
Section: Discussionmentioning
confidence: 90%
“…Despite reporting substantial challenges to delivering care, a majority of physicians felt they were able to deliver high quality care. This divergence is likely related to physicians defining high quality care outside of the domains of care assessed in our study 28,29 .…”
Section: Discussionmentioning
confidence: 90%
“…Si volvemos a considerar que los resultados quirúrgicos interesan a muchos es fundamental, hoy, poder conocer y comparar éstos entre diferentes instituciones y en una misma institución en el transcurso del tiempo [45][46][47][48] . Sabemos que para ello debemos ajustar los resultados de acuerdo a los factores de riesgo y que, finalmente, están determinados por múltiples factores 49,50 .…”
Section: Conclusionesunclassified
“…Examples of structural measures include surgical case volume, access to technology and equipment, and provider to patient ratios. The association between surgical case volume and health outcomes is one that has received notable attention in recent years, with research that has revealed a positive correlation between volume and outcomes, and policy discussions have begun to consider volume in reimbursement decisions [48]. The advantage of structural measures in assessing quality hinges on the presence of readily available data usually collected in administrative databases and therefore access to large volumes of data, as well as the opportunity for rapid review of easily analyzed data [49].…”
Section: Quality In Musculoskeletal Carementioning
confidence: 99%